Meningkatkan Penguasaan Kosakata Pada Siswa Menggunakan Aplikasi Quizlet - Rahayu, Sri; Nismawati, Nismawati; Saragih, Chelsi Ruth Meilin; Habeahan, Kaipah; Simarmata, Ronauli; Sidabalok, Hamidah (JURNAL PENDIDIKAN ROKANIA, 2024)
This research is motivated by the low vocabulary mastery of students at SMA Negeri 1 Kisaran in the 2024/2025 Academic Year. Although various techniques and approaches have been applied, students' abilities are still low. To overcome this problem, teachers need to find innovative teaching methods, such as utilizing technology through smartphone applications. This research was carried out from October to November 2024, involving 20 grade XI students. Data was collected through observation and tests, with a research design in the form of Classroom Action Research (PTK) which aims to solve problems and improve learning. The Quizlet application is used as a tool in technology-based learning. The results of the study showed an increase in student comprehension scores of 65.5% in Cycle I and 80% in Cycle II. Data analysis from Cycle II showed a significant improvement compared to the pretest in Cycle I, with all subjects achieving a minimum completeness score. The conclusion of this study is that the use of the Quizlet application is effective in improving students' vocabulary mastery. However, the improvement requires continuous adjustment of learning strategies, not just in one meeting